2019
DOI: 10.1177/0272431619891249
|View full text |Cite
|
Sign up to set email alerts
|

Brooding Concurrently and Prospectively Links Trait Positive and Negative Affect to Depressive Symptoms

Abstract: Recent theory and evidence support an integrated affective-cognitive model of adolescent depressive symptoms in which temperament predicts the use of maladaptive cognitive emotion regulation (ER) strategies which, in turn, predict depressive symptoms. We concurrently and prospectively investigated whether two cognitive ER strategies (dampening and brooding) mediated the effect of trait positive and negative affect on adolescent depressive symptoms. Young adolescents (11-14 years old) completed questionnaires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Trait affectivity has been shown to be a risk factor for developing depressive symptoms in adolescence (Mezulis et al, 2011 ; Verstraeten et al, 2009 ). Furthermore, research has shown that trait negative affectivity and trait positive affectivity relate to different responses to affective states, which can be harmful or protective of well-being (Rutter et al, 2020 ). Specifically, sadness as the emotional component of trait negative affectivity has been shown to be associated with the use of maladaptive responses to sadness (Peled & Moretti, 2010 ), and trait negative affectivity predicts the use of maladaptive responses to positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Trait affectivity has been shown to be a risk factor for developing depressive symptoms in adolescence (Mezulis et al, 2011 ; Verstraeten et al, 2009 ). Furthermore, research has shown that trait negative affectivity and trait positive affectivity relate to different responses to affective states, which can be harmful or protective of well-being (Rutter et al, 2020 ). Specifically, sadness as the emotional component of trait negative affectivity has been shown to be associated with the use of maladaptive responses to sadness (Peled & Moretti, 2010 ), and trait negative affectivity predicts the use of maladaptive responses to positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was observed in the indicators of rumination, in which only the brooding subscale (in contrast to the reflection scale) had a clinically relevant decrease. This particular style of negative repetitive thinking (brooding-focused rumination) has generally been related to the maintenance of depressive symptoms (Burwell & Shirk, 2007;Crane et al, 2007;Rutter et al, 2020), so changes in this type of rumination could indicate that an increase in selfcompassionate behaviors promotes the reduction of perseverative thought patterns characterized by negative, problem-focused self-evaluation without altering those repetitive thought patterns that focus on identifying possible solutions to the experienced problematic situation, favoring problem-solving (Fresnics et al, 2019;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%